Tiktok As A New Frontier For English Language Learning In Higher Education - Latifah, Siti Makrifatul; Syahira, Syahira; Arjuna, Ricky; Sulistyahadi, Sulistyahadi (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
In the current digital era, there are many tools or media that support English language learning by utilizing social media, such as TikTok which is one of the trending media.This research aims to explore the positive and negative experiences of students while using TikTok for learning English in higher education. The research method used is phenomenology with observation and interview techniques.The research indicate mostly positive and interesting learning experiences, driven by vocabulary growth, improved pronunciation and listening skills, and the platform's high accessibility, diverse content, and support for self-reflection and knowledge sharing. However, there are challenges such as distractions, content difficulty, technical issues, and a lack of structured learning. Nevertheless, TikTok significantly enhances student motivation.